(untitled) - Ramage, John D. (Needham Heights, MA, 1997)
This book offers engaging instruction in rhetoric and composition, a flexible sequence of comprehensive writing assignments, numerous examples of writing, and thorough guides to research and editing. Key Topics: Emphasizes writing as a problem-posing, problem-solving process of inquiry. Written in a friendly, encouraging tone reminiscent of Ramage and Bean's best-selling argument text, Writing Arguments. It offers balanced coverage of academic writing and personal and narrative forms and provides readers with a continuum for understanding differences between academic, thesis-driven, “closed-form” writing and personal, “open-form” writing. Accessible readings throughout clearly illustrate rhetorical principles and represent a balance between professional and student writers.
Keywords: English language,English language,Tiếng anh,Tiếng anh; Rhetoric,Grammar,Tu từ học,Ngữ pháp